The Psychometric Properties of the Norwegian version of Symptom Checklist-90-Revised (SCL-90-R) for youth and young adults (13-26 years) - Mundal, Ingunn P.; Ytreland, Kristin; Kaasbøll, Jannike (PsykTestBarn, 2022)
Description: The Symptom Checklist-90 Revised (SCL-90-R) is originally a versatile screening tool for psychological problems in people older than 13 years. The SCL-90 was developed by Derogatis and colleagues in 1973 and revised in 1976 to the SCL-90-R. The instrument was translated into Norwegian in the 1980s, and in 2010 Pearson Inc. published a Norwegian authorized edition with instructions for scoring and management. Authorized psychologists and physicians can run, score, and interpret the test. The selfreport test consists of 90 questions, and map symptom load within nine different symptom scales. In this review, we aimed to examine the measurement properties for SCL-90-R in Scandinavian studies including adolescents and young adults aged 13-26 years. Literature search: Of the 1359 references, 13 studies met the inclusion criteria. Ten studies were based on clinical samples (e.g., patients with behavioral disorders, depression, or eating disorders). Non-clinical samples included e.g., students, adopted children and children of divorced parents. Psychometics: None of the studies included psychometric properties, and most studies measured treatment effect or effect of other measures. Mean, standard deviation and internal consistency were reported. Conclusion: None of the studies included comprehensive information regarding measurement properties for SCL- 90-R for youth and young adults of 13–26 years. The evidence regarding the use of SCL-90-R in the is limited for this group.